Enabling responsible living - Fricke, Vera; Doyle, Declan; Thoresen, Victoria W.; Schrader, Ulf (Springer Berlin Heidelberg, 2013)
The book focuses on responsible living as the individual's contribution to sustainable development. We believe that sustainable development can only be achieved if individual freedom and responsibilities are balanced on a high level while taking social, ecological and economic needs into account. A crucial element to achieve this is to integrate different perspectives of stakeholders and co-create a joined approach through partnerships. While partnerships develop new opportunities for the stakeholders involved they also require a readiness for mutual understanding, respect and courage to co-create.